2022
DOI: 10.3390/ma15031083
|View full text |Cite
|
Sign up to set email alerts
|

Lubricity and Rheological Properties of Highly Dispersed Graphite in Clay-Water-Based Drilling Fluids

Abstract: Improving the tribological characteristics of water-based drilling fluids by adding graphene-based lubricants has garnered attention because of the potential for a range of inorganic-material-based additives at high temperature. In this study, we constructed a green and simple adsorption approach to prepare highly dispersed graphite using a cationic surfactant for graphite modification. The findings demonstrated that the prepared graphite was highly dispersed in water and had a low sedimentation rate and small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…A Cu target, ceramic X-ray tube, tube current of 40 mA, tube voltage of 40 kV, step size of 0.02° and scanning range of 5~60° (2θ) were used for the measurements. The variation in the interlayer spacing of sodium bentonite under different conditions was calculated using the Bragg equation (nλ = 2dsinθ) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…A Cu target, ceramic X-ray tube, tube current of 40 mA, tube voltage of 40 kV, step size of 0.02° and scanning range of 5~60° (2θ) were used for the measurements. The variation in the interlayer spacing of sodium bentonite under different conditions was calculated using the Bragg equation (nλ = 2dsinθ) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the modified graphite had no obvious effect on the rheological parameters of the drilling fluid. 78 …”
Section: Classification Of Environmentally Friendly Water-based Drill...mentioning
confidence: 99%
“…In addition, the modied graphite had no obvious effect on the rheological parameters of the drilling uid. 78 Table 6 showed the effects of the investigated nanographene lubricants on the rheological properties of drilling uids. The results showed that graphene, graphene oxide, and modied graphene all have no obvious effect on the rheological properties of drilling uid.…”
Section: Nano-lubricantsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shale gas mainly exists in mudstone, shale and other formations with hydrocarbon generation capacity in both adsorption and free states [12]. Although shale gas resources in China have great potential, shale gas resources are deeply buried and exploration and development started late [13]. In the process of shale gas exploitation, there are still major problems such as ultralow permeability of shale gas reservoir, reservoir protection, prevention of shale rock deformation and so on.…”
Section: Introductionmentioning
confidence: 99%